Boosting Grade 2A Islamic Elementary Students' Motivation via Hybrid Learning at Sari Bumi Sidoarjo - Naaziyah, Zumrotun; Wati, Tri Linggo (Indonesian Journal of Islamic Studies, 2024)
This study investigates the impact of hybrid learning on student motivation, focusing on class 2A students across varying levels of academic achievement. Employing a qualitative approach with a phenomenological lens, data was gathered through observation, interviews, documentation, and questionnaires. Validity was ensured through technical triangulation. The findings reveal a significant increase in student motivation following the implementation of hybrid learning. Students demonstrated heightened enthusiasm, attentiveness, earnestness, and active engagement in discussions and internet-based research. These results underscore the potential of hybrid learning to enhance student motivation, thus suggesting its relevance for contemporary educational practices. Highlights : Hybrid learning fosters student motivation: The study showcases how hybrid learning positively impacts students' motivation, resulting in increased enthusiasm and active participation in the learning process. Phenomenological inquiry: Employing a qualitative phenomenological approach, the research delves into the subjective experiences of students, providing rich insights into their perceptions and behaviors within the hybrid learning environment. Implications for educational practice: The findings underscore the potential of hybrid learning as a strategy to enhance student engagement and academic achievement, suggesting its relevance for contemporary educational practices worldwide. Keywords: Hybrid learning, Student motivation, Phenomenological approach, Academic achievement, Qualitative research